Hubungan Tingkat Konsumsi Makan dan Aktivitas Fisik dengan Status Gizi Anggota Ekstrakurikuler Paskibraka: The Relationship of Food Consumption Level and Physical Activities towards the Nutritional Status of Paskibraka Extracurricular Members - Fitria Hidayanti; Rahayu Dewi Soeyono (Amerta Nutrition, 2023)
Background: The Republic of Indonesia has a flag-hoisting team at the independence ceremony known as Paskibraka. Good nutritional status is one of the conditions for becoming a Paskibraka. Food consumption level and physical activity are factors that affect nutritional status. Objectives: This research aimed to determine the relationship between food consumption level and physical activity towards the nutritional status of students taking Paskibraka Extracurricular at SMAN 1 Bangkalan. Methods: This research used quantitative correlational research using a cross-sectional approach. The total sampling method was used to select 56 samples from students joining Paskibraka extracurriculars aged 15-16. While the independent variables included food consumption levels and physical activity, the dependent variable was nutritional status. The instruments were the respondent identity questionnaire, SQ-FFQ (Semiquantitative Food Frequency Questionnaire), and GPAQ (Global Physical Activity Questionnaire). The data were analyzed using Spearman's rank correlation.  Results: This research found that students' food consumption levels were normal (energy=76.8%, protein=58.9%, fat=73.21%, carbohydrates=69.64%). It also revealed that 75% had moderate physical activity and 89.29% had good nutritional status. Food consumption levels (energy p=0.011, fat p=0.024, and carbohydrates p=0.003) correlated with nutritional status, but protein consumption levels (p=0.141) and physical activity (p=0.626) did not correlate with it. Conclusions: Food consumption levels (energy, fats, and carbohydrates) correlated with nutritional status, but protein consumption and physical activity did not. A Paskibraka extracurricular student must pay attention to their daily food consumption and physical activity to have a good nutritional status.